Perlindungan Hukum bagi Konsumen yang dirugikan Akibat Pemakaian Masker Wajah Organik Ilegal yang dibeli Melalui Media Online - Miftakhul Aini; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Jurnal Analogi Hukum, 2022)
Many women want to have clean and healthy skin. So that there is an increase in perpetrators or unscrupulous actors who make masks with natural ingredients from nature which are used as beauty ingredients for women, but many ask for making natural mask makers to cheat by not registering their products with the relevant agencies for safety. The formulation of the problems raised in the writing of this thesis are: 1) What is the form of legal protection for consumers against the circulation of illegal organic face masks through online media? 2) How is the regulation of legal sanctions against perpetrators / sellers of illegal organic face masks through online media that are detrimental to consumers? The method used is a normative research method. The existence of legal guarantees to consumers against the circulation of illegal natural face masks through online intermediaries is regulated in Article 3, Article 4, and Article 5. In terms of legal sanctions, illegal face mask business actors receive sanctions in the form of administrative sanctions in which online site owners are blocked. temporarily by the relevant authorities and the revocation of business sales in the online business.